Joana's conclusion is not correct. The fact that her grouping led to no common binomial does not mean that the quadratic equation has no solutions. Let's analyze her steps:
- In Step 1, Joana rewrote the equation as \(4x^2 + 2x - 6x - 3 = 0\).
- In Step 2, she grouped the terms: \((4x^2 + 2x) + (-6x - 3) = 0\).
- In Step 3, Joana factored the first group as \(2x(2x + 1)\) and the second group incorrectly—one possible correction would have been to factor out \(-3\) to get \(-3(2x + 1)\).
Even though Joana encountered issues with grouping, quadratic equations can also be solved using the quadratic formula when factoring is complex or unhelpful. The equation \(4x^2 - 4x - 3 = 0\) should have solutions, which can be confirmed by using the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Here, \(a = 4\), \(b = -4\), and \(c = -3\):
\[ x = \frac{4 \pm \sqrt{(-4)^2 - 4 \cdot 4 \cdot (-3)}}{2 \cdot 4} \] \[ x = \frac{4 \pm \sqrt{16 + 48}}{8} \] \[ x = \frac{4 \pm \sqrt{64}}{8} \] \[ x = \frac{4 \pm 8}{8} \]
This gives two solutions:
- \(x = \frac{12}{8} = 1.5\)
- \(x = \frac{-4}{8} = -0.5\)
Thus, the answers exist.
Therefore, the correct response to Joana's conclusion is:
No, because she can still continue the steps even if the two groupings have no shared binomial.